Implementasi Manajemen Kurikulum dalam Meningkatkan Kinerja Guru - Lestiana, Lesi (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to analyze how the implementation of curriculum management can enhance teacher performance in schools. Effective curriculum management involves not only planning and implementation but also continuous evaluation and follow-up. Using qualitative research methods through observation, interviews, and documentation, this research was conducted in several schools in the X region. The findings indicate that structured curriculum management, supported by training and regular evaluation, has a significant impact on improving teacher performance. Teachers involved in curriculum planning and evaluation are better able to manage classrooms, apply innovative teaching methods, and improve student learning outcomes. In conclusion, effective curriculum management is a key factor in supporting teacher performance and improving the overall quality of education.